The The Impact of Coronavirus-2019 On General Health Anxiety Among Students of Iranian Medical Sciences: - Abiar, Sadaf; Modaresi, Farzaneh; Ansari, Amir; Karimi, Aliasghar; Eslamzadeh, Mahboubeh; Shekoohi, Fatemeh; Sabet, Hamid Reza (Galen Medical Journal, 2022)
Background: During the Coronavirus 2019 (COVID-19) outbreak, Iranian medical sciences students were at higher risk of contracting this virus because they were in infected environments. So, they are predisposed to high levels of anxiety that could worsen their lives. The determent of factors and levels of anxiety could be helpful to reduce anxiety and control its worse effects. Hence, this study aimed to measure the anxiety index and its factors among medical sciences students during the COVID-19 pandemic in Iran. Materials and Methods: In this cross-sectional study, an online survey was sent to students from 27 medical sciences universities in Iran from 20th December 2020 to 10th March 2021. The online survey consists of the Health Anxiety Inventory (HAI) for measured general health anxiety as well as the baseline characteristics of students. Results: 723 students responded, including 483 (66.8%) females and mean HAI score was 16.76 Â± 8.35. Based on our findings, gender, past medical, and drug history were significantly related to the high level of anxiety. However, there was no coloration between HAI scores with age, the field of study, study duration, university location, and attendance in the hospital and/or COVID-19 ward (PËƒ0.05). Conclusions: Students with notable past medical history and/or drug history and female students more than others were predisposed to anxiety in a pandemic such as COVID-19. Hence, in a pandemic situation, psychological care should concern them.